Hematopoietic cell transplantation and gene therapy for Diamond-Blackfan anemia: state of the art and science - Bhoopalan, Senthil Velan; Suryaprakash, Shruthi; Sharma, Akshay; Wlodarski, Marcin W. (Frontiers in Oncology, 2023)
Diamond-Blackfan anemia (DBA) is one of the most common inherited causes of bone marrow failure in children. DBA typically presents with isolated erythroid hypoplasia and anemia in infants. Over time, many patients experience multilineage hematopoietic cytopenias. Additionally, DBA is associated with increased risk of myeloid malignancy and solid tumors. As a prototypical ribosomopathy, DBA is caused by heterozygous loss-of-function mutations in over 20 ribosomal protein genes, with RPS19 being the most common. Corticosteroids are the only effective initial pharmacotherapy offered to transfusion-dependent patients aged 1 year or older. However, despite good initial response, only 20-30% remain steroid-responsive while the majority of the remaining patients will require life-long red blood cell transfusions. Despite continuous chelation, iron overload and related toxicities pose a significant morbidity problem. Allogeneic hematopoietic cell transplantation (HCT) performed to completely replace the dysfunctional hematopoietic stem and progenitor cells is a curative option associated with potentially uncontrollable risks. Advances in HLA-typing, conditioning regimens, infection management, and graft-versus-host-disease prophylaxis have led to improved transplant outcomes in DBA patients, though survival is suboptimal for adolescents and adults with long transfusion-history and patients lacking well-matched donors. Additionally, many patients lack a suitable donor. To address this gap and to mitigate the risk of graft-versus-host disease, several groups are working towards developing autologous genetic therapies to provide another curative option for DBA patients across the whole age spectrum. In this review, we summarize the results of HCT studies and review advances and potential future directions in hematopoietic stem cell-based therapies for DBA.